Pushed Past the Limit? : How Japanese Banks Reacted to Negative Interest Rates - Hong, Gee Hee (IMF Working Papers; Working Paper, 2018)
In this paper, we investigate how negative interest rate policy (NIRP) introduced in January 2016 by the Bank of Japan (BoJ) affected Japanese banks' lending and risk taking behavior. The BoJ's announcement was an unexpected surprise to the market and was followed by a sharp drop in equity prices of Japanese financial firms. We exploit the cross-sectional variation in the change of share prices on the day of the announcement to measure banks' differential exposure to NIRP. We show that more exposed banks increased their credit and took on more risk compared to banks that were less exposed to negative rates.